Temperature-dependent photoluminescence spectra of GaAsSb/AlGaAs and GaAsSbN/GaAs single quantum wells under different excitation intensities - Lourenço,S. A. (2007)
The mechanism for low-temperature photoluminescence (PL) emissions in GaAsSb/AlGaAs and GaAsSbN/GaAs strained-layer single quantum wells (SQWs), grown by molecular-beam epitaxy, is studied in detail, using PL spectroscopy as a function of temperature and excitation intensity. In all samples, the PL peak energy as well as the full width at half maximum (FWHM), as a function of temperature, present anomalous behaviors, i.e., the PL peak energy shows a successive red/blue/redshift (S-shaped behavior) and the FWHM shows a successive blue/red/blueshift ("inverted S-shaped curve") with increasing temperature. At sufficiently low excitation intensity and in a narrow temperature interval (50 - 80 K), the nitrogen-containing samples present two clear competitive PL peaks. The low-energy PL mechanism (8 - 80 K) is dominated by localized PL transitions, while the high-energy PL mechanism is dominated by the ground state (e1-hh1) PL transition. Additionally, these PL peaks show different temperature dependence with the low-energy PL peak, showing a stronger redshift than the high-energy PL peak. A competition process between localized and delocalized excitons is used to discuss these PL properties.